Pengaruh Panjang Pipa Inlet Terhadap Kinerja Pada Pompa Hidram - Mubarok, Afif; , Ir. Subroto, MT; , Nur Aklis. ST. MT (2016)
Water is a basic needs in everday life for humans, animals and plauts. To move water from low high places usually used electric motor pump or motor diesel. How ever, it makes its own difficulties when installing the electric installation for the water resources of the settlement reach too far, and fuel is also becoming incresingly expensive. There fore reuired an alternative tools one of them using a hydraulic pump. Which works with water pressure itself. This pesearch purposes is detormine effect of varition inlet pipe length of efficiency hydraulic pump. Research conducted using a hydraulic pump with the surface of reservoir remains high 3 m, press tube diameter 4 inch with a height if 70 cm. 1.5 inch diameter pump body and canductor pipe diameter of 0.5 inch and a height of 6 m. The vriation of the length inlet pipe with a length of 3 m, 3.5 m, 4 m, 4.5 m, 5 m. Refrieval debit pump by using a measuring cup every variation in the length of pipe inlet. The research resuts inlet pipe length variations affect the discharge and the pump efficiency. The variation of inlet pipe length of 3 m generate debit 0,02235 liter/second with a pump efficrency 23.95 %. The variation of inlet pipe 3.5 m. Generate debit 0.026 liter/second with a pump efficiency 27,85 %. The variation of inlet pipe 4 m. Generate debit 0.031 liter/second with a pump efficiency 32.21 %. The variation of inlet pipe 4.5 m, generate debit 0.03985 liter/second with a pump efficiency 41.83 % and variation of inlet pipe 5 m generate debit 0.04565 liter/second with a pump efficiency 48.91 %. Keywords : Hydraulic pump, length inlet pipe, pump debit, efficiency pump.